Factors for the adoption of generative artificial intelligence in the information technology sector in Klang Valley Malaysia - Priyanka, Hari Visnu (2024)
Generative Artificial Intelligence (Gen AI) is reshaping the information technology (IT) sector, driving innovation and enhancing business processes. This study investigates the factors influencing the adoption of Gen AI in the IT industry in Klang Valley, Malaysia, with two main objectives: to rank the factors driving adoption and to uncover the latent structures influencing this process. Using the Technology Organisation-Environment (TOE) framework, the research explores technological, organisational, and environmental factors through an extensive literature review. A quantitative methodology is employed, utilising surveys with IT professionals in Klang Valley experienced in AI technologies. The collected data is analysed using descriptive statistics and factor analysis and the sampling method is purposive sampling with the 70 participants of the sampling size. The study identifies four key factors crucial for the adoption of Gen AI: (1) Technological Capability, (2) Organisational Capacity, (3) Market Responsiveness, and (4) External Factors. These factors encompass various aspects of technological infrastructure, organisational readiness, market demand, and external influences that impact AI adoption. The study also explores the transformative effects of Gen AI on IT practices, focusing on one critical components: (1) Improved Information Technology Project Performance. Gen AI adoption significantly boosts IT project performance by streamlining decisionmaking, automating repetitive tasks, and enhancing data-driven insights. It also fosters innovation by enabling advanced problem-solving capabilities, ultimately driving higher operational efficiency. The findings provide a roadmap for IT organisations to successfully adopt and integrate Gen AI, offering valuable insights for decisionmakers and stakeholders in shaping a conducive environment for its widespread implementation. The study’s implications promise to elevate the IT sector's capabilities, improving productivity, collaboration, and innovation in the region.